The Implementation of CLT for Teaching English to Elementary Level Students at Islamic Boarding School Language Center - Hana, Mil’ul; Sulistyowati, Titis; rismiyanto, rismiyanto (Journal Prakarsa Paedagogia, 2025)
Communicative Language Teaching (CLT) is an approach that gives priority to language as a means of communication for real-life purposes, emphasizing interaction and the practical use of language. This study looks into how implements CLT in teaching English in elementary classes at the Language Center and how teacher’s perception views its effectiveness. This study uses a qualitative research design where data is collected through classroom observation and questionnaires completed by teacher and students in elementary level students. Observation allows the researcher to view the teaching practice in action, while interviews have covered the teacher’s opinions and experiences with CLT. Data analysis involve observations and responses to establish major themes relating to the effectiveness of CLT in enhancing student learning and engagement. The participants of this study are an English teacher and 8 students. The findings are the teacher implements CLT at Language Center in five principles; interaction through active participation, meaningful communication via real-life tasks, prioritizing fluency over accuracy, a student-centered approach, and authentic materials for relevance. The teacher also views CLT as a positive teaching method. It is shown by the effectiveness in motivating students and improving students’ communicative competence.